Determinasi Manajemen Laba: Peran Kepemilikan Manajerial, Leverage, dan Free Cash Flow - Asyira Khansa Rafifah; Wiwin Aminah (Politeknik Ganesha Medan, 2026)
This study examines the effect of managerial ownership, Leverage, and free cash flow on earnings management in infrastructure companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024. Prior studies report inconsistent findings and provide limited evidence for the infrastructure sector in recent periods. Based on agency theory, earnings management may arise from conflicts of interest between managers and shareholders. The study population comprises all infrastructure sector companies listed on the IDX during the research period. Purposive sampling was applied to select companies that were continuously listed and published annual reports throughout 2021–2024, resulting in 31 companies and 124 observations. A quantitative approach was used, utilizing secondary data from the companies’ annual reports and official IDX publications. Data analysis was conducted using panel data regression in EViews 13. The findings show that managerial ownership, leverage, and free cash flow simultaneously influence earnings management. Partially, however, only free cash flow has a significant positive effect, while managerial ownership and Leverage are not statistically significant. These results suggest that a higher level of free cash flow may encourage managers to engage in earnings management activities. This study contributes by providing recent empirical evidence and highlighting the dominant role of free cash flow in influencing earnings management in the infrastructure sector